Computational Model for Non-Isothermal Melt Spinning Flows: The Low Take Up Velocity Range - Ottone, Mariel Lorena (2002)
This work shows the interrelation between non-isothermal melt spinning flows and the isothermal extensional flow described through rheometry. This analysis uses the iterative numerical algorithm presented by Ottone and Deiber for non-isothermal melt spinning flows in the low take up velocity range. The results obtained for two take up velocities (1500 and 2500 m/min) are then shown in the extensional rheometric map composed by the lines of the steady state rheometric extensional viscosity as function of the extensional rate at different parametric temperatures. Then the search of scaling functions that allows one the formulation of master curves relating both flows is analyzed and discussed.